If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + x = 3x + -15 Reorder the terms: 15 + x = -15 + 3x Solving 15 + x = -15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 15 + x + -3x = -15 + 3x + -3x Combine like terms: x + -3x = -2x 15 + -2x = -15 + 3x + -3x Combine like terms: 3x + -3x = 0 15 + -2x = -15 + 0 15 + -2x = -15 Add '-15' to each side of the equation. 15 + -15 + -2x = -15 + -15 Combine like terms: 15 + -15 = 0 0 + -2x = -15 + -15 -2x = -15 + -15 Combine like terms: -15 + -15 = -30 -2x = -30 Divide each side by '-2'. x = 15 Simplifying x = 15
| 12+2x=24-2x | | (45-x)/x=23 | | 47=3+11h | | b(x^2)-ab=0 | | 7x-30=205 | | 7=w-(-7)5 | | x-10=6x+4 | | 6*x+4=x-11 | | x-26=10 | | 2x-2=-4(x-4) | | 10-3*x=x+4 | | -9=6+5v | | 3y+7=5y+1 | | 32x+(-32x+25)=12 | | 142,000,000/1.19 | | 12x-20=7x+20 | | f(20)=0.05x+3 | | 9c-4=26-c | | 50=5(3m-2) | | -15(-B)= | | 1/4=2/x | | -42=4t | | d/5-3=-4 | | 7+3t=5t-1 | | -0.6k-1+0.5k=3 | | g/10=10 | | 4x+-5y=-12 | | 276/6 | | 6c-3c+2d-4d= | | 2m+4=m-10 | | 0=x^2-20x+100 | | 5h/3=15 |